2021
DOI: 10.1038/s41598-021-87228-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an immunocompromised porcine model of human cancer for novel therapy development with pancreatic adenocarcinoma and irreversible electroporation

Abstract: New therapies to treat pancreatic cancer are direly needed. However, efficacious interventions lack a strong preclinical model that can recapitulate patients’ anatomy and physiology. Likewise, the availability of human primary malignant tissue for ex vivo studies is limited. These are significant limitations in the biomedical device field. We have developed RAG2/IL2RG deficient pigs using CRISPR/Cas9 as a large animal model with the novel application of cancer xenograft studies of human pancreatic adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…In addition to these improvements, we also anticipate that tumors in the pancreas will be easier to image and target compared to the healthy pancreas, which is an essential benefit of the pig model described in this work. Moving beyond the pancreas, in this report, we describe the use of multiple cell lines from cancers currently being evaluated by our research team to expand on the previously reported pancreatic tumors [103]. In the future, we plan to incorporate histotripsy data generated here for the liver and pancreas to refine the treatment parameters of these other cancers, defined here in subcutaneous models, including the use of PDX specimens and organoids to provide an even more robust and translational model for both human and veterinary patients with a wide range of cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these improvements, we also anticipate that tumors in the pancreas will be easier to image and target compared to the healthy pancreas, which is an essential benefit of the pig model described in this work. Moving beyond the pancreas, in this report, we describe the use of multiple cell lines from cancers currently being evaluated by our research team to expand on the previously reported pancreatic tumors [103]. In the future, we plan to incorporate histotripsy data generated here for the liver and pancreas to refine the treatment parameters of these other cancers, defined here in subcutaneous models, including the use of PDX specimens and organoids to provide an even more robust and translational model for both human and veterinary patients with a wide range of cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…These cell lines represent tumor types that we feel could significantly benefit from histotripsy-based applications and are areas of intense research focus in the field. This is the first report of the HepG2, U-251, and 4T1 tumors being successfully engrafted into a porcine model; there is a prior study that utilized the PANC-1 tumors to establish the potential of these animals to support xenografted tumor growth [103]. The 6 piglets were randomized and subcutaneously injected with 1.2x10 6 cells in 100 µL of Matrigel in the ear.…”
Section: B Characterization Of Rag2/il2rg Pig Tumor Modelmentioning
confidence: 99%
“…We elected to give a higher dose of AdCre (2 x 10 10 pfu) with the current experiments than what we used before (1 x 10 8 pfu), 18 i.e., >100-fold increase in the dose of AdCre. We also elected to administer IL-8 as an adjunct with the AdCre; this cytokine has been shown to mobilize the adenoviral receptor to the luminal membrane of epithelial cells, thereby enhancing viral entry.…”
Section: Resultsmentioning
confidence: 99%
“…4,8 Currently there are no validated large animal models for PC, though some proof-ofprinciple studies in swine have been published. [9][10][11] Swine have shown to be effective models in other fields, including trauma, transplantation, cardiovascular disease, and dermatologic conditions. 12,13 Swine have greater similarity to humans with respect to size, anatomy, physiology, pathophysiological responses, and coding sequence than do mice.…”
Section: Introductionmentioning
confidence: 99%
“…As pigs have similar physiology and more relevant body and organ sizes to humans compared to other laboratory species, porcine models can be used to understand disease progression and to test relevant doses of therapeutics or medical devices. To date, several porcine biomedical models have been generated, including those for cystic fibrosis (Rogers et al, 2008), cardiovascular disease (Turk et al, 2005), cancer (Schook et al, 2015;Hendricks-Wenger et al, 2021), phenylketonuria (Koppes et al, 2020), immunodeficiency (Suzuki et al, 2012;Lee et al, 2014), viral infection (Lei et al, 2016), and xenotransplantation (Lai et al, 2002). Moreover, gene editing has been used to improve carcass traits (Lai et al, 2006) of pigs and to confer resistance to viruses that plague the swine industry (Whitworth et al, 2016(Whitworth et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%